An evaluation of the empirical vancomycin dosing guide in pediatric cardiology - Yousif S. Alakeel; Yazeed Alahmed; Ghadah Alanazi; Bushra Alawbathani; Kadi Alshutwi; Meshary Almeshary; Fahad Aldhahri; Meshal Alshakrah (BMC, 2024)
Abstract Background Higher doses of vancomycin are currently prescribed due to the emergence of bacterial tolerance and resistance. This study aimed to evaluate the efficacy and safety of the currently adopted vancomycin dosing guide in pediatric cardiology. Methods This was a single-center prospective cohort study with pediatric cardiac patients, younger than 14 years, from June 2020 to March 2021. The patients received intravenous vancomycin (40 mg/kg/day divided every 6-8 h) according to the department's vancomycin medication administration guide (MAG) for at least three days. Results In total, 88 cardiac patients were included, with a median age of 0.82 years (IQR: 0.25-2.9), and 51 (58%) received cardiopulmonary bypass surgery (CPB). The majority (71.6%, n = 61) achieved a serum vancomycin level within the therapeutic range (7-20 mg/L). Infants, young children, and children exposed to CPB surgery had an increased incidence of subtherapeutic vancomycin levels, [7 (29.2%); P = 0.033], [13 (54.2%); P = 0.01], and [21 (87.5%); P = 0.009] respectively. After the treatment, 8 (10%) patients had an elevated Serum creatinine (SCr) and 2 (2.5%) developed acute kidney injury (AKI). However, no significant difference was found between the patients developing AKI or an elevated SCr and the group who did not, in terms of clinical, therapeutic, and demographic characteristics, except for the decreased incidence of SCr elevation in patients receiving an ACE inhibitor, [4 (36.4%); P = 0.036]. Conclusion Our institution followed MAG recommendations; however, subtherapeutic serum concentrations were evident in infants, young children, and CPB patients. Strategies to prevent AKI should be investigated, as the possible causes have not been identified in this study.